An update on the use of laser technology in skin vaccination. (November 2013) - Chen, Xinyuan; Wang, Ji; Shah, Dilip; Wu, Mei X
Vaccination via skin often induces stronger immune responses than via muscle. This, in line with potential needle-free, painless delivery, makes skin a very attractive site for immunization. Yet, despite decades of effort, effective skin delivery is still in its infant stage and safe and potent adjuvants for skin vaccination remain largely undefined. We have shown that laser technologies including both fractional and non-fractional lasers can greatly augment vaccine-induced immune response without incurring any significant local and systemic side effects. Laser illumination at specific settings can accelerate the motility of antigen-presenting cells or trigger release of 'danger' signals stimulating the immune system. Moreover, several other groups including the authors explore laser technologies for needle-free transcutaneous vaccine delivery. As these laser-mediated resurfacing technologies are convenient, safe and cost-effective, their new applications in vaccination warrant clinical studies in the very near future.